ANALISIS YURIDIS MEKANISME PEMAKZULAN PRESIDEN DAN WAKIL PRESIDEN MENURUT UUD NEGARA REPUBLIK INDONESIA TAHUN 1945 (SETELAH PERUBAHAN) - Zainal Arifin (Jurnal Hukum, 2020)
The term impeachment is not explicitly written in the constitution. In Big Indonesian Dictionary New Edition deposed mentioned is put positions; king abdicated. Prof. Jimly Asshiddiqie explained, impeachment is the uptake of the Arabic language which means derived from office. Or equal to the term 'impeachment ' in the constitution of Western countries. Dismissal of the President and / or Vice President of the mechanism is already provided for in Article 7A and 7B 1945. Prior to MPR dismiss both the President and / or Vice President , the mechanisms that must be taken is the first , the proposed dismissal of the President and / or Vice- president of the Board House of Representatives to the Assembly with only first submit a request to the Constitutional Court to examine, and decide upon the opinion of the House that the President and / or Vice President has violated the law in the form of treason against the State , corruption , bribery , criminal acts other heavy , or moral turpitude ; and / or opinions that the president and / or vice president is no longer eligible as president and / or vice president.